Adverse Events in Affiliated Hospitals of Mazandaran University of Medical Sciences - Saravi, Benyamin Mohseni (AVICENA, d.o.o., Sarajevo, 2014)
Due to the complexity of the hospital environment, its structure faces with multiple hazards. The risks whether by providing the care and whether by hospital environment endanger patients, relatives and care providers. Therefore, a more accurate reporting and analysis of the report by focusing on access to preventative methods is essential. In this study, hospitals' adverse event that has sent by affiliated hospitals of Mazandaran University of Medical Sciences to deputy for treatment has studied.